Suha koža - Gosenca Matjaž, Mirjam (Farmacevtski vestnik, 2021)
Dry skin or xerosis is a common skin condition that is attributed to lack of water in the stratum corneum. Although commonly related to skin diseases such as atopic dermatitis or psoriasis, it is of great importance to understand development and composition of dry skin when occurring as a condition itself seeing that at some stage of their lives, the majority of people will experience symptoms of dry skin. Due to new technologies, dry skin pathophysiology was evaluated at the molecular level, providing new insights in correlation of dry skin and impaired skin barrier function. In the following review, exogenous plus endogenous causes leading to clinical manifestation of dry skin are presented, being further upgraded with mechanism involved in dry skin cycle. Moreover, key factors of symptoms-based approach as a road map for diagnosis and treatment of dry skin, that was introduced recently, are briefly highlighted.
Keywords: dermatologija; klinična slika; Koža; kožna bariera; kseroza; suha koža